Probing luminescence of rare earth ions in natural pink fluorites using Raman microscopes. (29th May 2022) - Hagemann, Hans; Ayoubipour, Sareh; Delgado, Teresa; Schnyder, Cédric; Gnos, Edwin
Abstract: It is well‐known that many natural fluorite crystals contain rare earth ions. In this work, a series of pink fluorites is studied to demonstrate that the use of Raman microscopes allows to obtain high resolution emission spectra of trivalent rare earth ions. These emission spectra allow in principle to distinguish differences of the local environment related to the charge compensation necessary when the divalent Ca ion is replaced by a trivalent rare earth ion. The pink fluorites from the Alps have grown under hydrothermal conditions, which results in the incorporation of oxygen into the fluorite. In one sample from Juchlistock (Bern, Switzerland), a trigonal Eu 3+ ‐oxygen center is clearly identified. Interestingly, a pink fluorite from China (Huanggang Mine, Inner Mongolia, China) shows a quite different emission spectrum from those of the Alps. In this sample, the emission bands have much lower relative intensity compared with the intensity of the CaF2 Raman peak, indicating a much lower content of Er 3+ and Ho 3+ which emit around 520–560 nm. Literature examples show that Raman measurements of differently colored fluorite crystals can also present sharp rare earth spectra. By extension, it is thus possible to observe and identify emission spectra of rare earth ions in other mineral crystals using Raman microspectroscopy and avoid misassignments of the corresponding observed Raman spectra. Abstract : Raman microscopy allows to observe high‐resolution emission bands of rare earth impurities in natural fluorites and by extension also in other minerals. This is demonstrated in this work for spectra of various pink fluorites obtained with Raman microscopes.